FUNGSI GENDING AYAK WOLU PADA WAYANG KULIT GAGRAG JAWA TIMURAN KI SURWEDI - Jepri Ristiono (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2019)
ABSTARCTÂ This article originated from the interest of the author when he saw the phenomenon that occurred in the East Javanese leather puppet show Ki Surwedi, especially gending Ayak pathet Wolu which is very dominating. The discussion is focused on the gending function of Ayak pathet Wolu which concerns the relation of the song with the gamelan, so that it can conclude about the role and function of the song. Therefore, this article is qualitative with priority on the form of interview data and literature, and presented in descriptive-analytic. The data collected from various sources was analyzed using the function theory initiated by Alan P. Merriam in a book entitled The Anthropology of Music, translated by Hajizar in the form of "Concept as Source of Analysis". From this research, it can be concluded that the gending function of Ayak pathet Wolu in wayang Ki Surwedi is one of the art forms from ancestors that has been passed down from generation to generation. Therefore, it has become our collective duty to preserve it in order to avoid extinction.Â Kata kunci: ayak wolu, fungsi gendhing, wayang Jawa Timuran, Ki Surwedi